Predictors for recurrence of chronic osteomyelitis following long bones cavity defect replacement with synthetic materials - Alexander V. Afanasyev; Svetlana A. Bozhkova; Vasily A. Artyukh (Travmatologiâ i Ortopediâ Rossii)
Background. Recent scientific literature only has a few studies highlighting the factors affecting the development of recurrent infection after surgical treatment of chronic osteomyelitis.